Tujuan Pendidikan Perspektif Omar Mohammad Al-Toumy Al-Syaibany Dan Implikasinya Terhadap Pembelajaran Pendidikan Agama Islam Di Sekolah - Adesty, Hanifah; Syahidin, Syahidin; Firmansyah, Mokh. Iman (PT. Student RIhlah Indonesia, 2025)
The purpose of this study is to describe the purpose of education from the perspective of Omar Mohammad al-Toumy al-Syaibany and its implications for Islamic Religious Education Learning in Elementary Schools. This research uses a qualitative approach and literature study method. Based on the results of the study, the concept of Islamic education goals in al-Syaibany's perspective has a clear and comprehensive concept, the idea is very good if applied in learning Islamic Religious Education. The implications of both lie in the purpose of human life. where Islamic Religious Education aims to direct humans in achieving the true purpose of life, namely achieving happiness in the world and the hereafter. Both sources of education are the same, namely the Qur'an and Sunnah, which are the main references in the formulation of educational goals. The educational objectives of al-Syaibany's perspective also have implications for the planning, implementation and evaluation of Islamic Religious Education learning in schools. This is in line with the principles of Islamic education goals initiated by al-Syaibany which must be applied to the process of planning, implementing, and evaluating learning.